Experiences of Immigrant Women Living with Chronic Pain and their Caregivers: An Intersectional Approach - Khatibsemnani, Nasim (Université d'Ottawa / University of Ottawa, 2022)
Chronic pain is one of the most common health conditions, affecting nearly six million Canadian adults. Despite abundant research on chronic pain in general, there is limited knowledge on how racialized immigrant women experience living with chronic pain and how this relates to their broader social circumstances. The purpose of this qualitative, exploratory study is to understand living with chronic disabling pain as situated in and contextualized by the lived experiences of immigrant women residing in Ottawa, Ontario, and to explore the perspectives of the women's care partners as well as physicians providing care for chronic pain. Semi-structured interviews were conducted with 24 participants. The dissertation is guided by the social determinants of health framework and an intersectional lens. Four interconnected themes from the data analysis have been generated: (1) The trajectory and meaning of pain; (2) Reasons for pain and triggering factors; (3) Pain consequences; and (4) Coping and control. Findings indicate that chronic pain is a subjective, complex, biopsychosocial, and multidimensional phenomenon. Pain is a deeply personal experience linked with meaning. Results also highlight an association between the distribution of the social determinants of health during the life course and pain. Furthermore, the pain has profound, multidimensional impacts on the women and their families, and its treatment is a challenging task for health care professionals. In addition, the findings show that pain is often poorly recognized, underestimated, and inadequately managed. Finally, the results illustrate the perseverance and incredible resilience of the women and their carers. The findings provide several implications for policy, research, and practice.
Keywords: immigrants; chronic pain; intersectionality; social determinants of health; lived experience; population health; qualitative methodology